Hubungan Pengetahuan Teknik Mengeran dengan Kejadian Ruptur Perineum pada Ibu Bersalin di Puskesmas Julok Kecamatan Julok Aceh Timur Tahun 2024 - Murida.M; Ester Simanullang; Nopalina Damanik (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The results of the Population Census data carried out in 2020 showed that the maternal mortality rate reached 189 per 100 thousand live births. And based on these figures, Indonesia is ranked second highest in ASEAN, which is further than other countries such as Thailand, Malaysia, Vietnam and Brunei, which have achievements below 100 per 100 thousand live births. The maternal mortality rate is one of the important programs for the Ministry of Health (Kemenkes) to pay attention to. Therefore, through this, the Ministry of Health carries out a care program from before pregnancy, pregnancy, childbirth, babies. And a number of cases of pregnant women giving birth include anemia 48.9%, hypertension 12.7%, KEK 17.3% and complications as much as 28%. The impact of childbirth on maternal mortality is also something that cannot be separated from the occurrence of maternal death. As a health worker with high integrity, it is very necessary to implement Mother and Baby Care. Indicators of quality service are in the process of pregnancy care, postpartum delivery carried out by health workers to the mother. One of them is carried out in the delivery process by explaining to the mother the technique of pushing when the opening is complete or 10cm. Do not do forced pushing (Valsalva) or tell the mother to push forcibly before it is certain that the opening is complete. This is one of the strict prohibitions conveyed by Bergastrom in his book. The process of delivering a baby can generally cause tears in the vagina and perineum. So when leading pushing in a mother in labor, it is necessary to do so as not to cause irregular tears in the birth canal. However, the process of delivering a baby through the birth canal or through normal delivery requires deliberate tearing to widen the birth canal. However, for further action, it is necessary to do hecting or stitches on the episiotomy wound which aims to restore the original shape of the perineal incision scar and stop bleeding as well as healing.